2021
DOI: 10.3389/fimmu.2021.652383
|View full text |Cite
|
Sign up to set email alerts
|

Using Routine Laboratory Markers and Immunological Indicators for Predicting Pneumocystis jiroveci Pneumonia in Immunocompromised Patients

Abstract: BackgroundPneumocystis jiroveci pneumonia (PJP) is the most common opportunistic infection in immunocompromised patients. The accurate prediction of PJP development in patients undergoing immunosuppressive therapy remains challenge.MethodsPatients undergoing immunosuppressive treatment and with confirmed pneumocystis jiroveci infection were enrolled. Another group of matched patients with immunosuppressant treatment but without signs of infectious diseases were enrolled to control group.ResultsA total of 80 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Consistent with previous study, we showed that LDH in the PCP group was significantly higher than that in the non-PCP group, which could be due to the lung injury. 17 However, we showed that there was no significant difference in the counts of total lymphocytes, CD3+ lymphocytes, and CD8+ lymphocytes between PCP and non-PCP groups. In contrast, we observed that patients with PCP were associated with a significant decrease of CD4+ T cells in blood and CD4+/CD8+ ratio in both circulation and BAL.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Consistent with previous study, we showed that LDH in the PCP group was significantly higher than that in the non-PCP group, which could be due to the lung injury. 17 However, we showed that there was no significant difference in the counts of total lymphocytes, CD3+ lymphocytes, and CD8+ lymphocytes between PCP and non-PCP groups. In contrast, we observed that patients with PCP were associated with a significant decrease of CD4+ T cells in blood and CD4+/CD8+ ratio in both circulation and BAL.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with previous study, we showed that LDH in the PCP group was significantly higher than that in the non-PCP group, which could be due to the lung injury. 17 However, we showed that there was no significant difference in the counts of total lymphocytes, CD3+ lymphocytes, and Tang et al 17 showed that both CD4+ and CD8+ cells were decreased in non-HIV PCP patients. Ling et al showed that a decrease in CD4+/CD8+ ratio could predict PCP in non-HIV children.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Additionally, lactate dehydrogenase (LDH) is an important predictive marker for patients with PJP. LDH in patients with PJP was significantly higher than in non-PJP controls ( 27 ). Neutropenia is a risk factor of PJP.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, many studies manifested that the blood routine parameters and the rate between them may use as indicators for state, development, and prognosis of diseases ( 32 , 33 ). AS is a common chronic rheumatic disease, and we systematically determined the relevance between new-onset AS and blood routine parameters (WBC, L, L%, N, N%, M, M%, PLT, MPV, PCT, PDW, RBC, HGB, and HCT) and the ratio between them (LMR, PLR, NLR, dNLR, PMR, MNR, PNR, and SII).…”
Section: Discussionmentioning
confidence: 99%